ANALISIS POTENSI PREBIOTIK GROWOL: KAJIAN BERDASARKAN PERUBAHAN KARBOHIDRAT PANGAN - Puspaningtyas, Desty Ervira; Sari, Puspita Mardika; Kusuma, Nanda Herdiyanti; Helsius SB, Debora (PERSATUAN AHLI GIZI INDONESIA, 2019)
Disease treatment and prevention can be done by providing appropriate dietary therapy, such as the use of functional food. Growol, cassava fermented food, is potentially developed as functional food. Cassava fermentation process into growol can change growol?s prebiotic potency. Aim of this study was to know growol?s prebiotic potency as a functional food based on carbohydrate changes. This was an observational laboratory study. Samples of this study were cassava and growol. Cassava used in this study was Manihot esculenta Crantz. The prebiotics potency was seen from carbohydrate, reducing sugar, sucrose and dietary fiber content. Carbohydrate was analyzed using carbohydrate by difference, while reducing sugar and sucrose were analyzed using Nelson-Somogyi and enzymatic hydrolysis. Gravimetric AOAC enzymatic was used to measure dietary fiber content. Dependent t-test was used to determine the prebiotic potency differences in growol and cassava. Fermentation of cassava into growol statistically reduced total sugar (p=0.001), reducing sugar (p=0.002), and sucrose (p=0.003). Furthermore, fermentation process of cassava into growol increased carbohydrate (p=0.038); insoluble dietary fiber (p=0.005); soluble dietary fiber (p=0.048); and dietary fiber (p=0.005). In conclusion, growol can be potentially developed as functional food in terms of carbohydrate changes, and it expected to be used in disease treatment and prevention. Further studies can examine changes of other nutritional compounds in growol due to fermentation. Moreover, study about health effects of growol administration is needed to be done.